The fragile road towards peace and democracy: insights on the effectiveness of international support to post-conflict Burundi - Karina Mroß (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
How can international engagement support fragile states on their path towards peace and democracy? In light of perpetuating and recurring armed conflict all over the world, this question is of utmost importance to many policymakers. In order to better understand factors influencing the effectiveness of this support, this present paper analyses international support for peace and democratisation in the so far relatively successful case of Burundi. After one decade of civil war, a seriously weakened Burundi state faced the double challenge of overcoming not only its violent past but also the legacy of socio-political exclusion and ethnic antagonism. Since then, the international community has engaged strongly in supporting Burundi on its road towards peace and democracy. The country has made remarkable achievements in this regard – such as adopting a new constitution in 2005 and dissolving its rebel armies through integration and demobilisation. Recently, however, progress has stalled. The 2010 elections were overshadowed by the opposition's boycott, further narrowing the already limited political space. Each of these three processes was shaped by political power struggles and had a decisive impact on Burundi's future development. By analysing each of them in detail, this research generates valuable insights into internal dynamics of post-conflict peace and democratization as well as international support thereto. The research was guided by three explanatory factors (hypotheses) drawn from academic literature, which suppose that 1) prioritising stability over democracy , 2) choosing cooperative over coercive forms of cooperation , and 3) high levels of coordination enhance the effectiveness of international support for peace and democracy. However, only the last presumption was confirmed: coordination of donor activities did indeed have a positive impact on its effectiveness. Yet, contrary to expectations from the literature, prioritising stabilisation has hampered democratisation and actually reduced the effectiveness of democracy support. Similarly, the Burundi case calls for qualifications regarding the second explanatory factor: depending on the circumstances, either cooperative or coercive measures rendered external support more effective.
Keywords: 330; Demokratie und Autokratie; Sicherheit; Frieden und fragile Staaten